Some Remarks on the Linguistic Community of the Russian Old Believers’ Dialect in Poland and in the Baltic Area - Гжибовский, Стефан (Slavistica Vilnensis, 2018)
[full article, abstract in Russian; abstract in Lithuanian and English] In 2001, Valery N. Chekmonas (1936–2004), an excellent expert on Slavic and Baltic languages, advanced a hypothesis that Old Believers’ Russian dialects in the Baltic area form a rural dialectal community, partly due to their origin. This view was repeated in his paper that was prepared together with Nadezhda Morozova and published in 2007. The Old Believers’ dialect in Poland, investigated by scholars from Nicholas Copernicus University in Toruń (Poland) for several years, appears to be the most western point of the dialects at issue and seems to give additional arguments to Chekmonas’s view. This paper examines the lexical items that may be of Polish origin or are consonant with Polish words. A partial investigation of the collected material (about 15% of all records) allows us to affirm that many of them are present in Russian dialects in Lithuania, Latvia and Estonia. Some of them are restricted to the Baltic area, but most of them can be found in the Russian dialects close to that area (Pskov, Novgorod, Smolensk, Briansk), others in the different Siberian dialect and, what is very significant, in the Belarusian as well. Thus, the investigation supports Valery N. Chekmonas’s hypothesis. Further researches should provide new arguments.